Two New Spectrophotometric Methods for the Determination of Isoniazid in Bulk Form and Tablet Dosage Form. (2019)
To develop two new spectrophotometric methods for the analysis of isoniazid in bulk form and tablets. The methods involved condensation of isoniazid with salicylaldehyde and diazo coupling with diazotized p-nitroaniline. Critical factors were optimised; evidence for new product formation, selection of analytical wavelengths, temperature and time and solvent for dilution. Validation was carried out according to ICH guidelines. The new methods were used for isoniazid tablets. Isoniazid formed an imine and azo adduct readily with the two reagents at 30 ⁰C after 5 and 20 mins, and determined at 405 and 420 nm, respectively. Low LODs were obtained for the two methods and recoveries were generally above 98%. The methods were successfully adopted for the assay of isoniazid in tablets and there were no significant differences in the contents when compared with the official titrimetric method of analysis. The methods could find application as in-process method in pharmaceutical industries.